CHAT: Alondra Nelson, "The Social Life of DNA" Twitter Storify export - Strauber, Chris (Tufts Archival Research Center, 2017)
PDF export of a Storify created from tweets sent during Alondra Nelson's lecture "The Social Life of DNA" delievered as part of the Melon Sawyer Seminar in Global Humanities.